An Active Ground Fault Location Method for Low-Voltage DC Lines Based on DFFT - Fulu CAO; Jinbin ZHAO; Chao PAN; Ling MAO; Keqing QU (Zhongguo dianli)
For the problem of locating ground faults in low-voltage DC cable lines containing power electronic transformers, a single-ended volume fault location method using power electronic transformers with active injection is proposed for rapid fault detection and restoration of power supply. A sinusoidal voltage signal with 210 Hz frequency is injected into the low voltage side through the medium voltage port of the power electronic transformer. The characteristic signal will be transmitted to the low voltage side capacitor through the high frequency transformer, and the characteristic parameters of the capacitor voltage and current are extracted and identified using the fast Fourier transform to calculate the line impedance after the fault. At the same time, a secondary curve fitting construction curve method is used to reduce the impedance errors caused by spectral leakage and frequency domain reactance waveform oscillation and to obtain the accurate fault location. Finally, the PSCAD/EMTDC simulation results have verified the effectiveness of the proposed method for locating the ground faults of low-voltage DC lines containing power electronic transformers with noise interference resistance and certain transition resistance resistance.